2020
DOI: 10.1177/1178221820924026
|View full text |Cite
|
Sign up to set email alerts
|

How are Substance Use Disorder Treatment Programs Adjusting to Value-Based Payment? A Statewide Qualitative Study

Abstract: Healthcare systems are implementing value-based payment (VBP) arrangements in efforts to incentivize cost-effective, high quality of care. These arrangements represent a major shift for substance use disorder (SUD) treatment providers who may need to make changes to their clinical and business operations to meet new demands for quality under value-based contracts. This qualitative study was conducted in the context of New York State’s efforts to implement VBP among SUD treatment providers to understand their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thus, the change to value-based payments could be perceived as adding regulatory and financial risks for both public and private sectors. Similar to challenges identified in our study, in a study of value-based care for substance use disorder treatment, researchers identified providers’ buy-in to value-based concepts as a key workforce challenge [ 11 ]. Additionally, we found developing a template for value-based contracts was perceived as a lower priority compared to other organizational and state initiatives due to limited agency bandwidth and competing priorities during the COVID-19 global pandemic.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, the change to value-based payments could be perceived as adding regulatory and financial risks for both public and private sectors. Similar to challenges identified in our study, in a study of value-based care for substance use disorder treatment, researchers identified providers’ buy-in to value-based concepts as a key workforce challenge [ 11 ]. Additionally, we found developing a template for value-based contracts was perceived as a lower priority compared to other organizational and state initiatives due to limited agency bandwidth and competing priorities during the COVID-19 global pandemic.…”
Section: Discussionmentioning
confidence: 70%
“… 13 Further, this demonstration of value should include input from patients who are informed and selective about their healthcare options. 14 The systematic uptake of MBC and the assessment of performance via quality measures can help clinicians meet these expectations. In addition, a quality improvement program that includes systematic uptake of MBC can help ensure patients receive the same level of high-quality, evidence-based care regardless of the treatment setting.…”
Section: Background/rationalementioning
confidence: 99%
“…Multiple systemic reviews have concluded that addiction treatment in the United States has large gaps in quality of care and limited capacity for clinical program improvement, and there are no agreed upon quality metrics for the SUD treatment field [67][68][69][70][71][72]. Notably, the workforce has limited levels of education or professional training to implement process change initiatives to improve clinical outcomes [67,70,71,73]. Because of this limitation, the proposed intervention will draw from our current research [74] based on principles of process improvement and the iPARIHS framework to coach OTPs on changing protocols and workflows to adopt more flexible THD [75][76][77][78][79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%